The Validity of Student Worksheets and Student Textbooks Inquiry Training Model on The Colligative Properties of Solution - Pratikno, Putri; Suyono, Suyono; Agustini, Rudiana (International Journal for Educational and Vocational Studies, 2020)
This study is development research of student worksheets and student textbooks using the inquiry training model to support the learning of the colligative properties of solution. The purpose of this study was to produce valid student worksheets and student textbooks. Student worksheets and student textbooks are developed using the ADDIE (Analyze, Design, Development, Implement, and Evaluate) design. The validity measured includes construct validity and content validity. The validity of the device was assessed by three validators using a validation sheet. The validation result data were analyzed descriptively quantitative and descriptive qualitative. The results of data analysis show that the student worksheets and student books developed have reached a valid category with the mode of score ranging from 3 to 4.